2021
DOI: 10.1055/s-0041-1731901
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Oncological Outcomes of Multidisciplinary Management of Ewing’s Sarcoma of Clavicle: A Single-Center Experience

Abstract: Objectives Ewing’s sarcoma is best treated using a multidisciplinary approach. We discuss the functional and oncological outcomes of clavicular Ewing’s sarcoma which has been sparsely reported in literature. Materials and Methods We retrospectively evaluated patients who underwent resections for Ewing’s sarcoma of clavicle from January 2002 to December 2017. The study end points were locoregional recurrence free survival (LRFS), disease-free survival (DFS), and overall survival (OS) at 3 and 5 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…There are different opinions as to whether reconstruction is necessary after excision, and studies have reported shoulder dysfunction and scapular dyskinesia [ 7 ]. Reconstructive surgery could expose the patient to the risk of surgery, although there is no functional superiority [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are different opinions as to whether reconstruction is necessary after excision, and studies have reported shoulder dysfunction and scapular dyskinesia [ 7 ]. Reconstructive surgery could expose the patient to the risk of surgery, although there is no functional superiority [ 9 ].…”
Section: Discussionmentioning
confidence: 99%